2011
DOI: 10.1016/j.ajhg.2011.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BRCC3 Deubiquitinating Enzyme Leads to Abnormal Angiogenesis and Is Associated with Syndromic Moyamoya

Abstract: Moyamoya is a cerebrovascular angiopathy characterized by a progressive stenosis of the terminal part of the intracranial carotid arteries and the compensatory development of abnormal and fragile collateral vessels, also called moyamoya vessels, leading to ischemic and hemorrhagic stroke. Moyamoya angiopathy can either be the sole manifestation of the disease (moyamoya disease) or be associated with various conditions, including neurofibromatosis, Down syndrome, TAAD (autosomal-dominant thoracic aortic aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 34 publications
(40 reference statements)
0
93
0
Order By: Relevance
“…7 Recently Xq28 deletions removing MTCP1/ MTCP1NB and BRCC3 have been shown to cause a type of X-linked familial moyamoya syndrome. 8 A number of growth factors are thought to be associated with MMD. Because of the extensive collateral formation defining MMD, research has focused on vascular and angiogenic factors.…”
Section: Genetics and Pathophysiologymentioning
confidence: 99%
“…7 Recently Xq28 deletions removing MTCP1/ MTCP1NB and BRCC3 have been shown to cause a type of X-linked familial moyamoya syndrome. 8 A number of growth factors are thought to be associated with MMD. Because of the extensive collateral formation defining MMD, research has focused on vascular and angiogenic factors.…”
Section: Genetics and Pathophysiologymentioning
confidence: 99%
“…1), none of these genes is a plausible candidate for the phenotypic features observed in the SHAM syndrome patient or a symptomatic female carrier. The role for BRCC3, a ubiquitin ligase involved in DNA damage response complexes, in the development of vessels was elegantly shown in the original report by Miskinyte et al using a zebrafish model (with endothelium-specific expression of brcc3 rescuing the angiogenesis defects) (Miskinyte et al, 2011). In another report, BRCC3 was demonstrated to be a component of a deubiquitinating complex that was implicated in protection of cardiomyocytes from cellular stress-related apoptosis (Cilenti et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Further studies into BRCC3 role are warranted at both clinical and mechanistic level, in particular it is not known whether the role of BRCC3 in moyamoya is related to its role in DNA damage signalling. Of note is the relatively frequent occurrence of secondary moyamoya following cranial irradiation that is likely dependent on DNA damage or hypoxia signalling that could be similar to those associated with BRCC3 loss (Miskinyte et al, 2011;Sigdel et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[13][14][15] Novel molecular genetics tools also recently led to the identification of several genes involved in other stroke conditions, such as moyamoya disease and monogenic moyamoya syndromes, opening avenues to understanding the mysteries of their pathophysiology. 16,17 Finally, it is helpful to inform patients that conventional modifiable risk factors remain relevant, despite an unfavorable genetic background. The prospective, community-based Japan Collaborative Cohort Study, which involved >110 000 individuals, found that a parental history of stroke imparted a population-attributable fraction of risk of stroke death of 5.4% in men and 4.3% in women.…”
Section: February 2013mentioning
confidence: 99%